2012
DOI: 10.1021/nn3035155
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Protein Adsorption and Macrophage Uptake of Gold Nanoparticlesviaa Hydrophobic Shield

Abstract: Polyethylene glycol (PEG) surface coatings are widely used to render stealth properties to nanoparticles in biological applications. There is abundant literature on benefits of PEG coatings and their ability to reduce protein adsorption, to diminish non-specific interactions with cells, and to improve pharmacokinetics, but very little discussion of the limitations of PEG coatings. Here, we show that physiological concentrations of cysteine and cystine can displace methoxy-PEG-thiol molecules from the gold nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
215
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(222 citation statements)
references
References 74 publications
5
215
2
Order By: Relevance
“…Spleen tissue had significantly increased TUNEL positive cells (predominantly localized to the red pulp) relative to control tissue with an average of 88±15 positive cells for experimental samples versus an average of 19±3 positive cells for control samples (P,0.001) (Figure 6). While TEG gold nanoparticles are collected promiscuously through the spleen, likely by macrophages per Larson et al's 13 work characterizing ligand-exchanged PEG-coated particles ( Figure 4D and E), these results suggest that the nanoparticles taken up in the spleen red pulp, by perhaps reticular meshwork macrophages as previously described, are toxic. 19 Thus, both TEG-and PEG-coated nanoparticles are toxic, albeit to different organs.…”
Section: Teg Particles Induce Apoptosis In the Spleensupporting
confidence: 71%
See 3 more Smart Citations
“…Spleen tissue had significantly increased TUNEL positive cells (predominantly localized to the red pulp) relative to control tissue with an average of 88±15 positive cells for experimental samples versus an average of 19±3 positive cells for control samples (P,0.001) (Figure 6). While TEG gold nanoparticles are collected promiscuously through the spleen, likely by macrophages per Larson et al's 13 work characterizing ligand-exchanged PEG-coated particles ( Figure 4D and E), these results suggest that the nanoparticles taken up in the spleen red pulp, by perhaps reticular meshwork macrophages as previously described, are toxic. 19 Thus, both TEG-and PEG-coated nanoparticles are toxic, albeit to different organs.…”
Section: Teg Particles Induce Apoptosis In the Spleensupporting
confidence: 71%
“…To determine whether intracellular concentrations of glutathione are sufficient to induce ligand exchange reactions with TEG nanoparticles, 13 a TEG nanoparticle preparation was mixed 1:1 with glutathione dissolved in water to yield aliquots with a final glutathione concentration of 0.1 mM (low concentration), 1 mM (low cellular concentration), 5 mM (medium cellular concentration), and 10 mM (high cellular concentration).…”
Section: Gold Nanoparticle-ph Interaction Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that physiological concentrations of thiolcontaining molecules such as cysteine easily displace, for example, thiolated Polyethylene-glycol (PEG) from the surface of Au NPs [50,51]. The (partial) loss of the ligand, however, has far-reaching consequences as it impacts colloidal stability of the core NP, changes the adsorbed protein profile, and may lead to the complete loss of any functional grafted ligands such as fluorescent dyes, antibodies, or drug molecules.…”
Section: Cell Culture Mediamentioning
confidence: 99%